Quantitative assessment and comparison of architectural design elements of selected residential buildings in Davao City - Mariscotes, Patricia Almie Louise R. (2018)
This study was conducted to quantitatively assess the aesthetics of selected residential buildings in Davao City. The researcher assessed sixty-four (64) houses in total, thirty two (32) of which are considered to be Heritage Houses by Museo Dabawenyo and the remaining half is Modern Houses that are equally taken among the three (3) district of Davao City.Each house was assessed using Birkhoff's Aesthetic Measure which considers two main factors: Order and Complexity. Order has six (5) components, namely: symmetry, repetition, equilibrium, disposition, colour harmony, and negative factor. On the other hand, component has four (4) components and these are: form complexity. ornaments, silhouette differentiation, and colour contrast. These components are scored through a scale of 0-2 according to the scoring index. These scores are used to compute for the aesthetic measure (order/complexity) of each house and is interpreted afterwards. The components are documented by the researcher through photo documentation.After gathering all the necessary data required, it is analyzed using qualitative description based on the basic statistics being used to analyse the data. Heritage houses have a result of order is much higher than complexity while modern houses has higher order and lower complexity. It means that heritage houses have higher order with least number of details while modem houses are houses with fairly aesthetic building with average level of excitement.